2015
DOI: 10.1007/s00705-015-2389-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of group A rotavirus strains detected in children with diarrhea admitted to Nigerian hospitals in 2013

Abstract: Group A rotaviruses (RVA) are the leading cause of acute gastroenteritis (AGE) in children worldwide and cause up to 455,000 deaths annually, mostly in developing countries. During 2013, 66 RVAs from children with AGE admitted to four Nigerian hospitals were investigated. The G3P[6], G1P[8] and G2P[4] genotypes predominated. The VP7 and/or VP4 genes of 18 G3P[6]/[8]/[4], six G2P[4], three G12P[8]/[4], and two G1P[8] RVA strains were sequenced. The G3P[6] strains belonged to lineage G3-III and were different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 24 publications
3
15
0
Order By: Relevance
“…The impact of unusual strains on RV evolution has yet to be determined, however, such strains could provide the opportunity for the introduction of novel P or G genes into human population via reassortment events [ 22 ]. The non-typeable strains included in the study were the RV strains which could not be typed either for any of the G (5.1%) or P (4.1%) genotypes or for both genotypes (1.3%) which is lower than that observed (6.1% G-P non-typeable) in neighboring Nigeria [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of unusual strains on RV evolution has yet to be determined, however, such strains could provide the opportunity for the introduction of novel P or G genes into human population via reassortment events [ 22 ]. The non-typeable strains included in the study were the RV strains which could not be typed either for any of the G (5.1%) or P (4.1%) genotypes or for both genotypes (1.3%) which is lower than that observed (6.1% G-P non-typeable) in neighboring Nigeria [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alkali et al [ 28 ] detected G4P[8], G4P[6], and G3P[6] strains among children from Sokoto. The most recent report on rotavirus molecular characterization reported unusual G3 strains not previously identified in Africa [ 29 ]. Another landmark report was that of Adah et al [ 30 ] that showed evidence of a possible intra host recombinant G8P[1] human rotavirus strain HMG035 which was very similar to that of a bovine A5 strain from Thailand.…”
Section: Epidemiology Of Rotavirus In Nigeriamentioning
confidence: 99%
“…Majority of the VP7 sequences recovered between the years 2010 and 2013 belonged to genotypes G3 and G12 and were recovered in two separate outbreaks. The first outbreak took place in Ile-Ife in South Western, Nigeria, in 2011 [ 26 ], while the second outbreak took place in Enugu, Eastern Nigeria, Ile-Ife South West, Nigeria, and Maiduguri Northern Nigeria, in 2013 [ 29 , 33 ]. Virtually all the G3 isolates, particularly the 2011 outbreak strains, fell within lineage III.…”
Section: Molecular Diversity Of Rotavirus Vp7 (G) and Vp4 [P] Genomentioning
confidence: 99%
See 2 more Smart Citations